E-Learning in the teaching of law at Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia: an experience in creating storyboards for the Islamic Family law course - Abdul Hak, Nora (2005)
The paper describes one of the efforts taken in the implementation of e-learning at the Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia. The rationale for e-learning in teaching law courses is to improve the quality of education of law students, as well as to introduce to the students new technologies in legal education. It is also to make the teaching of law more interesting and interactive. The Kulliyyah is currently utilising a learning management system of Meditech LearningCare in its implementation of e-learning. This system is managed by the Multimedia and IT Unit of AIKOL. At the Kulliyyah all lecturers and registered students will be given access to the LMS. To get access to the information contained in the lecturers’ portfolio, the registered students have to subscribe to that portfolio. The lecturers are expected to update their portfolio from time to time to facilitate online discussion with the students. In the portfolio, the lecturer has included a wide range of information including personal information, explanation about the course, notes, reflective comments, announcements and course works such as assignments, projects, tests etc. Consequent to the implementation of e-learning, a project on repurposing content for e-learning has been carried out between the Kulliyyah and the Content Capital Sdn. Bhd. This paper explains the experience of the lecturer involved in creating the storyboard, which was later developed into a courseware for teaching and learning law subjects. In this project the subject involved was the Islamic Family Law.